Menantea Franchise Agreement Case Analysis Reviewed from the KUHPer - Nabila Tiara Deviana; Urbaniasi Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
The development of the Indonesian economy was followed by the development of legal forms of agreements. Nowadays many people start a business by buying a business system or what is known as a franchise which in Indonesian is called a franchise. Franchising comes from the word Wara which means more and Profit which means profit. Literally franchising means that franchising is a business that provides more profits. In addition, according to the Indonesian Franchise Association (AFI), what is meant by franchising is a system of distributing goods or services to end customers, where the owner (franchisor) gives rights to individuals or companies (franchisees) to carry out business with a brand, name, system, procedure and ways that have been determined beforehand in a certain period of time covering a certain area. Menantea is a tea beverage product that was founded in 2021. Menantea does not only sell tea drinks but also food in the form of chicken and potatoes. Menantea officially opened on April 10 2021. However, only 11 days later, alias on August 21 2021, they are reported to have offered a franchise. In fact, this is something that is not fair. Because, a business that can be offered as a franchise must have an STPW (Franchise Registration Certificate), one of the conditions is to fulfill the profit offering prospectus. In this case the author will discuss legal protection and legal remedies that can be taken by the Franchisee in the Menantea franchise agreement.